Anwar's remark on intruders draws flak - News Straits, Times (New Straits Times, 2013)
KUALA LUMPUR: A political analyst has hit out at opposition leader Datuk Seri Anwar Ibrahim for his fresh attempt at politicising the Lahad Datu standoff, while reiterating the call for political parties to remain bipartisan.